2010 International Conference of Soft Computing and Pattern Recognition 2010
DOI: 10.1109/socpar.2010.5686083
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the MSCI EURO index based on fuzzy grammar fragments extracted from European Central Bank statements

Abstract: Abstract-We focus on predicting the movement of the MSCI EURO index based on European Central Bank (ECB) statements. For this purpose we learn and extract fuzzy grammars from the text of the ECB statements. Based on a set of selected General Inquirer (GI) categories, the extracted fuzzy grammars are grouped around individual content categories. The frequency at which these fuzzy grammars are encountered in the text constitute input to a Fuzzy Inference System (FIS). The FIS maps these frequencies to the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Regarding the research using the documents published by financial institutions and companies, Milea et al ( 2010 ) predicted the Morgan Stanley Capital International (MSCI) euro index (upwards, downwards, or constant) based on fuzzy grammar fragments extracted from a report published by the European Central Bank. Brown and Tucker ( 2011 ) showed that the market price reaction weakens despite the increase in disclosed information, and the usefulness of management's discussion and analysis (MD&A) has declined.…”
Section: Related Studymentioning
confidence: 99%
“…Regarding the research using the documents published by financial institutions and companies, Milea et al ( 2010 ) predicted the Morgan Stanley Capital International (MSCI) euro index (upwards, downwards, or constant) based on fuzzy grammar fragments extracted from a report published by the European Central Bank. Brown and Tucker ( 2011 ) showed that the market price reaction weakens despite the increase in disclosed information, and the usefulness of management's discussion and analysis (MD&A) has declined.…”
Section: Related Studymentioning
confidence: 99%
“…Ito et al proposed a text-visualizing neural network model to visualize online financial textual data and a model called gradient interpretable neural network (GINN) to clarify why a neural network model make the result in financial text mining [18,19]. Milea et al predicted the MSCI EURO index (3 classes: up, down, and stay) based on the fuzzy grammar of European Central Bank (ECB) statement text [20]. Xing et al proposed a method for building a semantic vine structure among companies on the US stock markets using text mining and extended this method by implementing the similarity between all pairs of vector representations of descriptive stock company profiles into an asset allocation task to reveal the dependence structure of stocks and optimize financial portfolios [21].…”
Section: Related Workmentioning
confidence: 99%
“…Abbasi and Chen, (2007b;2007a) analysed hate and violence in extremist web forums using manually constructed affect lexicons. Financial index and stock prediction based on SA was explored by (Lee et al, 2013;Makrehchi et al, 2013;Milea et al, 2010;Zhang et al, 2011b).…”
Section: Implicit Featuresmentioning
confidence: 99%